Penerapan Metode Gamifikasi Dengan Pendekatan Hasthalaku Pada Pelajaran Produk Kreatif dan Kewirausahaan - Asri Pujihastuti; Teguh Waluyo; Budi Murtiyasa (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
Learning in the technology 4.0 era provides many challenges for teachers. Effective learning does not only require good teaching methods but is also determined by the use of interesting and interactive learning media. One of the media that can increase interest in student learning is gamification media, namely the addition of game elements in learning to increase motivation, involvement and interaction of teachers and students in learning. This method can also increase learning motivation by giving prizes or badges to students with the highest encouragement in learning. The purpose of this study was to determine student motivation through classpoint gamification media at SMKN 7 Surakarta in the subject of Creative Products and Entrepreneurship. The research method used is a qualitative descriptive approach through Participatory Action Research (PAR) by means of observation or observation of teaching and learning activities and interviews with students. The results showed that the use of classpoint gamification media increased learning interest and student involvement in learning from the usability, cognitive and psychomotor aspects of students. This is because classpoint gamification media has features that support interactive learning activities and can motivate students to get the best results in games or quizzes.